Managing maintenance resources - Kelly, Anthony, M. Sc.; ScienceDirect eBooks (Oxford : Elsevier Butterworth-Heinemann, 2006)
Plant asset management is a holistic approach to managing maintenance. Practical, accessible and business centred, these books provide a complete guide to understanding, planning, organising and managing maintenance. Together they cover the needs of any organisation with assets to maintain and manage. World-renowned expert Tony Kelly identifies real-world business aims and delivers a complete methodology for developing maintenance objectives, formulating a maintenance strategy, and designing and implementing maintenance systems that deliver. With full coverage of key techniques including TPM, RCM and CMMP, this is the complete maintenance management resource. * The most comprehensive guide to all aspects of managing and executing maintenance * World-renowned author with stand-out ability to cover this huge subject comprehensively and rigorously * Fully developed for professionals and students, with both theory and practice and cases form ranging from the process industries to customer services systems.
Strategic Maintenance Planning, 0750669926 -- Managing Maintenance Resources, 0750669934 -- Maintenance Systems & Documentation, 0750669942.
Includes index.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Plant maintenance -- Management; Material requirements planning; Plant maintenance -- Management -- Case studies; Material requirements planning -- Case studies; Material requirements planning; Plant maintenance -- Management; Onderhoud; Bedrijfsorganisatie; Strategische planning; Electronic books